Rancangan Pengembangan Wisata Bukit Pecaringan Untuk Peningkatan Ekonomi Masyarakat Desa Jarak - Resolute, Layra Cholifah Lordly; Huda, Syamsul; Utami, Anisa Fitria (CV. ITTC INDONESIA, 2023)
Jarak Village has charming natural potential for natural tourism locations. One of the natural attractions in the Jarak Village is Pecaringan Hill. The development of the Pecaringan Hill area is carried out with the aim of increasing the welfare of the village and villagers. Apart from that, the development of this tourist area also aims to enable the Jarak Village to optimize its potential to become a tourist village and attract many tourists. The service activity uses the data collection method and the regional design stage. The design documentfor the development of the Pecaringan Hill area was openly accepted by the village goverment. The design of this thourism development will make the tourism sector of the Jarak Village become more developed.